A comprehensive life cycle assessment study on potential power supply options for a chlor alkali production plant - Ayca, Sumeyya; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This research study aims to present a comparative analysis of the emission rates of toxic gases from various power sources suitable to meet the energy demand of a chlor-alkali plant producing hydrogen (H2), using a life cycle methodology. The emissions are then assessed using this methodology. The Greenhouse Gases, Regulated Emissions and Energy Use in Transport (GREET) software program is employed to analyze the power sources. The emission data from eight different energy sources that are part of the power generation segment at the proposed facility are analyzed comparatively. The subject matter data include carbon dioxide (CO2), methane (CH4), nitrogen oxides (NOx), sulfur oxides (SOx), volatile organic compounds (VOC), particulate matter pollutants (PM10), fine particles (PM2.5), nitrous oxide (N2O) and volatile organic carbon (POC). According to the life cycle assessment results, among the energy sources considered, wind power generated for hydrogen production using Pathway 1 appears to be the most environmentally benign option with the lowest emission rates while the oil-fired power generation option through Pathway 8 is the most harmful option with the highest emission rates. The emission values obtained in Pathway 1, where the electricity demand is met in a chlor-alkali production facility where 1 kg of hydrogen is produced, are as follows: CO2 1.65 kg, CH4 0.0032 kg, NOx 0.005 kg, SOx 0.0031 kg, VOC 0.00039 kg, PM10 0.00045 kg, PM2.5 0.0047 kg, N2O 0.000029 kg and POC 0.00014 kg. Excluding hydrogen transportation from the tube-trailers emission value, the highest emission from Pathway 1 as an energy source in the chlor-alkali production facility producing 1 kg of hydrogen is CO2 gas with 1.31 kg, and the lowest emission is N2O gas with 0.027 kg.
Keywords: Chlor-alkali process; Climate change; Energy; Energy sources; Environmental protection; Global warming; Life cycle assessment; EMISSION FACTORS; TECHNOLOGIES; GENERATION; INDUSTRY; OZONE; COAL; Computer Science; Engineering